Beyond valence: a meta-analysis of discrete emotions in firm-customer encounters - Kranzbühler, Anne-Madeleine (Springer Nature, 2020)
Distinguishing between consumers’ positive and negative affect is a popular approach in both marketing research and practice, but such valence-based approaches sacrifice specificity and explanatory power. As emotions of the same valence can greatly differ with regard to their underlying appraisal patterns, they also differently affect consumer judgment and behavior. Our meta-analysis of 1035 effect sizes (N = 40,777) across 10 discrete emotions shows that analyzing discrete emotions clearly outperforms models of core affect (valence and arousal) when studying firm–customer encounters. Specifically, we find that the greatest impact stems from the medium-arousal emotion of gratitude and that positive emotions show consistently stronger effect sizes than do negative emotions. We also examine how effects are moderated by situational characteristics of the experience triggering the emotion. Based on our findings, we develop recommendations that help marketers identify and manage consumers’ emotions more effectively.